Spatiotemporal dynamics of information encoding revealed in orbitofrontal high-gamma - Erin L. Rich (Nature Portfolio, 2017)
High gamma activity (HGA) and local neurons encode similar information, but it’s unclear if this is true when neurons are heterogeneous, as in the orbitofrontal cortex (OFC). Here, Rich & Wallis show that HGA in OFC is closely related to neuron firing, but reveals clearer spatiotemporal dynamics.